Safety evaluation of an extension of use of the food enzyme β‐glucosidase from the non‐genetically modified Penicillium guanacastense strain AE‐GLY - EFSA Panel on Food Enzymes (FEZ); Holger Zorn; José Manuel Barat Baviera; Claudia Bolognesi; Francesco Catania; Gabriele Gadermaier; Ralf Greiner; Baltasar Mayo; Alicja Mortensen; Yrjö Henrik Roos; Marize L. M. Solano; Monika Sramkova; et al. (EFSA Journal)
Abstract The food enzyme β‐glucosidase (β‐d‐glucoside glucohydrolase, EC 3.2.1.21) is produced with the non‐genetically modified Penicillium guanacastense strain AE‐GLY by Amano Enzyme Inc. A safety evaluation of this food enzyme was made previously, in which EFSA concluded that this food enzyme did not give rise to safety concerns when used in four food manufacturing processes. Subsequently, the applicant has requested to extend its use to include three additional processes and to revise the use levels. In this assessment, EFSA updated the safety evaluation of this food enzyme when used in a total of seven food manufacturing processes. The dietary exposure was calculated to be up to 0.206 mg total organic solids (TOS)/kg body weight (bw) per day in European populations. Using the no observed adverse effect level reported in the previous opinion (943 mg TOS/kg bw per day), the Panel derived a margin of exposure of at least 4578. Based on the previous evaluation, the assessment of the new data and the revised margin of exposure, the Panel concluded that this food enzyme does not give rise to safety concerns under the revised intended conditions of use.